Comparative analyses of ubiquitin-like ATG8 and cysteine protease ATG4 autophagy genes in the plant lineage and cross-kingdom processing of ATG8 by ATG4. Issue 11 (1st November 2016) - Seo, Eunyoung; Woo, Jongchan; Park, Eunsook; Bertolani, Steven J.; Siegel, Justin B.; Choi, Doil; Dinesh-Kumar, Savithramma P.
ABSTRACT: Autophagy is important for degradation and recycling of intracellular components. In a diversity of genera and species, orthologs and paralogs of the yeast Atg4 and Atg8 proteins are crucial in the biogenesis of double-membrane autophagosomes that carry the cellular cargoes to vacuoles and lysosomes. Although many plant genome sequences are available, the ATG4 and ATG8 sequence analysis is limited to some model plants. We identified 28 ATG4 and 116 ATG8 genes from the available 18 different plant genome sequences. Gene structures and protein domain sequences of ATG4 and ATG8 are conserved in plant lineages. Phylogenetic analyses classified ATG8 s into 3 subgroups suggesting divergence from the common ancestor. The ATG8 expansion in plants might be attributed to whole genome duplication, segmental and dispersed duplication, and purifying selection. Our results revealed that the yeast Atg4 processes Arabidopsis ATG8 but not human LC3A (HsLC3A). In contrast, HsATG4B can process yeast and plant ATG8s in vitro but yeast and plant ATG4s cannot process HsLC3A. Interestingly, in Nicotiana benthamiana plants the yeast Atg8 is processed compared to HsLC3A. However, HsLC3A is processed when coexpressed with HsATG4B in plants. Molecular modeling indicates that lack of processing of HsLC3A by plant and yeast ATG4 is not due to lack of interaction with HsLC3A. Our in-depth analyses of ATG4 and ATG8 in the plant lineage combined with results of cross-kingdom ATG8 processing by ATG4 further support the evolutionarily conserved maturation of ATG8. Broad ATG8 processing by HsATG4B and lack of processing of HsLC3A by yeast and plant ATG4s suggest that the cross-kingdom ATG8 processing is determined by ATG8 sequence rather than ATG4.